2018
DOI: 10.1093/schbul/sby018.831
|View full text |Cite
|
Sign up to set email alerts
|

S44. Lumateperone (Iti-007) for the Treatment of Schizophrenia: Placebo-Controlled Clinical Trials and an Open-Label Safety Switching Study

Abstract: BackgroundLumateperone (ITI-007) is a first-in-class investigational agent in development for the treatment of schizophrenia. Acting synergistically through serotonergic, dopaminergic and glutamatergic systems, lumateperone represents a new approach to the treatment of schizophrenia and other neuropsychiatric disorders. Lumateperone is a potent antagonist at 5-HT2A receptors and exhibits serotonin reuptake inhibition. Lumateperone also binds to dopamine D1 and D2 receptors acting as a mesolimbic/mesocortical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The combined effects of this compound (strong block of 5-HT2ARs, dopamine modulation, serotonin reuptake inhibition and indirect glutamatergic activity) resulted in reducing positive and negative symptoms, as well as in improving social functioning of SCZ patients, with low rates of EPS or metabolic side effects. 19 Since many compounds binding to 5-HT2ARs also exhibit high affinity to 5-HT2CRs, it was hypothesized that 5-HT2CR antagonism may reduce the activity of dopaminergic neurons in mesolimbic and nigrostriatal pathways. 63 However, the role of 5-HT2CRs in the pathophysiology of SCZ is still poorly understood and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined effects of this compound (strong block of 5-HT2ARs, dopamine modulation, serotonin reuptake inhibition and indirect glutamatergic activity) resulted in reducing positive and negative symptoms, as well as in improving social functioning of SCZ patients, with low rates of EPS or metabolic side effects. 19 Since many compounds binding to 5-HT2ARs also exhibit high affinity to 5-HT2CRs, it was hypothesized that 5-HT2CR antagonism may reduce the activity of dopaminergic neurons in mesolimbic and nigrostriatal pathways. 63 However, the role of 5-HT2CRs in the pathophysiology of SCZ is still poorly understood and requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…17 In this regard lumateperone, an investigational drug displaying high-affinity binding to the 5-HT2AR as well to D1 and D2Rs, but with minimal binding affinity for 5-HT2CR, histaminergic and muscarinic receptors, received its first global approval in the USA for the treatment of SCZ in adults, in view of its efficacy with a favorable safety profile. [18][19][20] So far, other 5-HTR targeted compounds are emerging as possible pharmacological treatments for SCZ. Therefore, the purpose of this review is to evaluate the main preclinical and clinical pharmacological findings concerning the therapeutic potential of 5-HTR-targeted therapies in SCZ patients.…”
Section: Introductionmentioning
confidence: 99%
“…Risperidone also had the highest dropout rate, calling into question whether more poorly responsive patients dropped out early on risperidone. 56 Across the 3 trials, lumateperone had minimal adverse effects, with sedation/somnolence and dry mouth being present in at least 5% and at twice the rate as with placebo.…”
Section: Treatment Optionsmentioning
confidence: 98%
“…7,10 Lumateperone has been shown to indirectly modulate glutamatergic activity by increasing phosphorylation of the GluN2B subunit of the N -methyl- d -aspartate channels as a result of the mTOR protein pathway. 11,12…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…17 Trial NCT02469155 demonstrated that after 6 weeks of treatment for schizophrenia, the doses of lumateperone 20 and 60 mg were not efficacious because they failed to separate from placebo. 12 Trial NCT03249376 was a 6-week phase III study for bipolar depression in which lumateperone 42 mg separated from placebo after 8 days of treatment in the total MADRS score; the difference was maintained through day 43 ( E = −0.56; P < 0.0001). 18 Finally, an open-label 12-month study of lumateperone 42 mg showed that 39% of the patients were PANSS responders, with ≄20% PANSS improvement from baseline.…”
Section: Clinical Trialsmentioning
confidence: 99%